Perbedaan Bentuk Kekerasan dalam Rumah Tangga Ditinjau dari Usia saat Menikah dan Tingkat Pendidikan - Nanda Rizki Rahmita; Haiyun Nisa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
Domestic violence (KDRT) is a global problem found in all cultures and communities. Perpetrators or victims of domestic violence come from different backgrounds, such as those from all ages, ethnicities, income levels, or education levels. Domestic violence victims can experience various types of violence including psycho-physical violence and control violence. Age at marriage and level of education affect the types of domestic violence experienced by victims. The research method used is a quantitative method with a comparative research on 86 subjects who experienced domestic violence. Data analysis used Crosstab and Chi-Square Test for Independence analysis which showed the significance value of the form of domestic violence. These results indicate that there are no differences in forms of domestic violence in terms of age at marriage and education level. Viewed from age at marriage and education level, the subjects of the study experienced more control violence compared to psycho-physical violence.